2019
DOI: 10.11604/pamj.2019.32.166.18481
|View full text |Cite
|
Sign up to set email alerts
|

Superbugs-related prolonged admissions in three tertiary hospitals, Kano State, Nigeria

Abstract: Introduction Superbugs are pathogenic micro-organism and especially a bacterium that has developed resistance to the medications normally used against it. As the superbug family increases, the need for appropriate diagnostic, treatment, prevention and control strategies cannot be over emphasized. Therefore, this work determined the distribution of superbug bacteria among patients on prolonged hospital admissions in three tertiary hospitals of Kano state, Nigeria. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 12 publications
1
17
1
Order By: Relevance
“…This can be supported by a study that reported the presence and increase of MRSA in Many hospitals of several countries in Africa [24]. On the contrary our findings are different from the studies of Nouetchognou et al and Bashir et al who conducted in and Yaounde University Teaching Hospital in Cameroon and three tertiary hospitals, Kano state, Nigeria, where Klebsiella spp were the most frequently isolated bacterial nosocomial pathogens from all units and all studied hospitals respectively [6,25].…”
Section: Profile and Prevalence Of Bacteria Isolated According To Thecontrasting
confidence: 49%
“…This can be supported by a study that reported the presence and increase of MRSA in Many hospitals of several countries in Africa [24]. On the contrary our findings are different from the studies of Nouetchognou et al and Bashir et al who conducted in and Yaounde University Teaching Hospital in Cameroon and three tertiary hospitals, Kano state, Nigeria, where Klebsiella spp were the most frequently isolated bacterial nosocomial pathogens from all units and all studied hospitals respectively [6,25].…”
Section: Profile and Prevalence Of Bacteria Isolated According To Thecontrasting
confidence: 49%
“…In our study, S. pyogenes resistance to penicillin, ceftriaxone, and amoxicillin/clavulanic acid was 24%, 26% and 32%, respectively. In other African countries, Streptococci species showed higher rate of resistance (40%) to ceftriaxone [ 22 ]. However, a report in Tanzania indicated a resistance rate to ceftriaxone (4.4%), penicillin (38.3%) and amoxicillin/clavulanic acid (40.4%) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Confirmatory investigations are needed to determine if prolong or delayed healing of oropharyngeal lesions could be linked to: drug-resistance (1), non-adherence to prescription guidelines (2)), abuse of antibiotics with sub-lethal doses (3-4), re-infection (5), progression of HIV disease to AIDS (1-2) or resistant opportunistic infections (27). With the increasing notorious nature of yeast as predominant opportunistic pathogens in oropharyngeal lesions of HIV/AIDS patients, it becomes necessary to determine the characteristic vulnerability of yeasts to routine prophylactic antifungal agents to 9 achieve better intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Amphotericin B-resistant clinical isolates of C. tropicalis have also been found (11,58). Minimum inhibitory concentration (MIC) of tested antifungal agents (Table 1) There is evidence to suggest that intermittent versus continuous dosing, the amount of drug administered, the length of treatment (27), the immune status of the patient and alterations in the membrane structure or in the sterol-to-phospholipid ratio in the membrane may be associated with resistance (53,11,58). The success or failure of antifungal drug therapy is dependent not only on the drug, but also on the immune status of the host and a combination of azoles and cytokines may be an important therapeutic strategy for resistant fungal infections in immunocompromised individuals.…”
Section: Resultsmentioning
confidence: 99%